The University-College Idea: A Critical Analysis - Dennison, John D. (Canadian Journal of Higher Education, 1992)
Following the recommendations of a committee on access to postsecondary education in British Columbia, a new institution, the university-college, was established in three locations in the province. This study is an analysis of the university-college idea. The results indicate that, while the university-college has produced many beneficial results, it has also created a number of difficult issues. These issues include the survival of the comprehensive college curriculum, governance, expectations of faculty performance and the missions of the university-college itself. Each issue is discussed in this paper.